(untitled) (Research, Society and Development, 2022)
This text aims to elucidate basic concepts for the strengthening of interprofessional education in health. It is a theoretical-reflective text, built on the basis of a Narrative Review. It took as its source the scientific literature on the topic of Interprofessional Education (IPE). The materials were located and selected from a free search in the Virtual Health Library (BVS), in the Scientific Electronic Library Online (SciELO) and in the Editora Rede Unida website, submitted to successive in-depth readings, seeking to apprehend the concepts in focus, and presented in the narrative synthesis format. The literature shows that the term uniprofessional refers to the process in which the knowledge of an area predominates. Multiprofessional knowledge refers to the process in which there is a certain coordination between disciplines. Interprofessionality, on the other hand, occurs when professionals learn from and about each other, and transprofessionality takes a higher stage, characterizing the fusion of certain fields of knowledge. Still, the concept of teamwork is characterized as a complementarity of practices, while collaboration has the sense of cooperation. It is important to emphasize that the elucidation of concepts and the reflection carried out in this work are important in the sense of contributing to the formation and professional practices being consistent with new, more advanced ways of producing health and, thus, with the strengthening of the Unified Health System.